2013
DOI: 10.2478/10004-1254-64-2012-2189
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen Analogues Reduce 2-chloroethyl Ethyl Sulphide Toxicity in A-431 Cells

Abstract: Vesicants are potent blistering agents. The prototype vesicant is sulphur mustard gas, fi rst used in World War I, which still has no effective antidote. We used a mustard gas surrogate 2-chloroethyl ethyl sulphide (CEES) to study the ability of resveratrol (RES) and pterostilbene (PTS), two well-established stilbene antioxidants, ebselen (EB-1), an organoselenium compound, and three EB-1 analogues (EB-2, EB-3, and EB-4) to reduce CEES toxicity in human epidermoid carcinoma cells (A-431). Following a 24-hour i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…EB-1 is an anti-inflammatory antioxidant compound that is under investigation for reperfusion injury ( Aras et al, 2014 ), stroke ( Yamaguchi et al, 1998 ), hearing loss ( Kil et al, 2021 ) and bipolar disorder ( Singh et al, 2013 ). Previous research in our lab has shown the edema-reducing and anti-vesicant ( Lulla et al, 2014 ), anti-bacterial ( Chan et al, 2007 ), anti-fungal ( Billack et al, 2010 , Orie et al, 2017 ) and cyto-protective ( Hardej and Billack, 2007 , Pino and Billack, 2008 , Pino et al, 2013 ) properties of EB-1. The second compound tested here was HC, a corticosteroid with immunosuppressant activity (Issekutz, 1983, Coutinho and Chapman, 2011 ), is used topically in the treatment of various inflammatory skin conditions such as allergic rashes, eczema and psoriasis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…EB-1 is an anti-inflammatory antioxidant compound that is under investigation for reperfusion injury ( Aras et al, 2014 ), stroke ( Yamaguchi et al, 1998 ), hearing loss ( Kil et al, 2021 ) and bipolar disorder ( Singh et al, 2013 ). Previous research in our lab has shown the edema-reducing and anti-vesicant ( Lulla et al, 2014 ), anti-bacterial ( Chan et al, 2007 ), anti-fungal ( Billack et al, 2010 , Orie et al, 2017 ) and cyto-protective ( Hardej and Billack, 2007 , Pino and Billack, 2008 , Pino et al, 2013 ) properties of EB-1. The second compound tested here was HC, a corticosteroid with immunosuppressant activity (Issekutz, 1983, Coutinho and Chapman, 2011 ), is used topically in the treatment of various inflammatory skin conditions such as allergic rashes, eczema and psoriasis.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, HN2 exhibits a very complex mechanism of toxicity that involves many macromolecules and cell signaling pathways ( Korkmaz et al, 2006 , McManus and Huebner, 2005 , Tewari-Singh and Agarwal, 2016 ). Our group previously reported that HN2 triggers numerous responses in cultured skin cells in vitro , including damaged nuclear DNA, increased lipid peroxidation and apoptosis via activation of caspases 3 and 9 ( Lulla et al, 2013 , Pino and Billack, 2008 , Pino et al, 2014 ), and that the organoselenium compound ebselen (EB-1) reduces the toxicity of both HN2 ( Hardej and Billack, 2007 , Lulla et al, 2014 ) and the sulfur half mustard CEES in vitro ( Pino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the determined values of logP for Eb -calculated (2.92) [33] and experimentally estimated (2.8) [34] we could conclude that is a hydrophobic molecule. Therefore, predominantly should be present in the oily core of formed nanocapsules.…”
Section: Discussionmentioning
confidence: 99%
“…31 Use of ebselen (2-phenyl-1, 2-benzisoselenazol-3(2H)-one), a peroxynitrite scavenger, and 3 analogs have been shown to reduce CEES toxicity in vitro. 54 Also, an NM exposure model has been shown to reduce histopathology but not NM-induced elevation in lung iNOS levels. 55 Melatonin, a scavenger of both reactive nitrogen and oxygen species, when given to NM-exposed rats, was able to reduce NM-induced increase in iNOS, glutathione peroxidase activity, and reduced inflammation in the lung.…”
Section: Antioxidant Drugmentioning
confidence: 99%